"With my head on the pillow": Sovereignty, Ethics, and Evil among Undercover Police Investigators. (29th March 2016) - Feldman, Gregory
Abstract: Based on intensive ethnographic fieldwork among an undercover police investigative team in a southern European Union member state, I argue that moments arise when this team acts "ethically" in spite of the legal and policy mandates surrounding their work. I understand ethical action to include action that people undertake because they refuse to bear any responsibility (active or passive) for events that they deem to be "evil, " lest such events become constitutive of their own personhood. This situation would preclude individuals from living in agreement with themselves. To this end, the article details some basic conditions in which this team works when operating outside of the law. This ethnographic analysis points to a form of political sovereignty that depends squarely upon particular speaking subjects rather than transcends and homogenizes those subjects as made evident in Agamben's "state of exception" argument. Those conditions include their particular place in the investigative process; egalitarianism among particular subjects; deep familiarity with each other; and an understanding of similarities between themselves and the targets of their investigations. Though fleeting in its appearance, the impetus to political action and a sovereign form premised upon particular speaking subjects can be well understood by developing certain implications in phenomenological anthropology and the anthropology of ethics. Most important among them is the need for mutual recognition among particular speaking subjects as political equals.